2021
DOI: 10.1186/s13613-021-00844-2
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood types and sepsis mortality

Abstract: Background We aimed to determine if the ABO blood types carry different risks of 30-day mortality, acute kidney injury (AKI), and endothelial damage in critically ill patients with sepsis. This was a retrospective cohort study of three independent cohorts of critically ill patients from the United States and Scandinavia consisting of adults with septic shock. We compared the 30-day mortality across the blood types within each cohort and pooled the results in a meta-analysis. We also estimated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…In two separate studies, Reilly et al demonstrated that blood group A is associated with increased risk for ARDS in sepsis and trauma, possibly due to dysfunction of endothelium and microvasculature, as indicated by altered levels of biomarkers (e.g., soluble thrombomodulin and selectins) [ 14 , 15 ]. These findings are supported by results from a large study of critically ill sepsis patients evaluating the ABO blood group and biomarkers of endothelial damage, which demonstrated moderately decreased mortality for blood group B [ 12 ]. In the present study, the potential effect of the ABO-blood group did not influence morbidity and mortality outcomes for any of the sepsis ( n = 3016), septic shock ( n = 1366) or ARDS ( n = 5642) subgroups.…”
Section: Discussionmentioning
confidence: 54%
“…In two separate studies, Reilly et al demonstrated that blood group A is associated with increased risk for ARDS in sepsis and trauma, possibly due to dysfunction of endothelium and microvasculature, as indicated by altered levels of biomarkers (e.g., soluble thrombomodulin and selectins) [ 14 , 15 ]. These findings are supported by results from a large study of critically ill sepsis patients evaluating the ABO blood group and biomarkers of endothelial damage, which demonstrated moderately decreased mortality for blood group B [ 12 ]. In the present study, the potential effect of the ABO-blood group did not influence morbidity and mortality outcomes for any of the sepsis ( n = 3016), septic shock ( n = 1366) or ARDS ( n = 5642) subgroups.…”
Section: Discussionmentioning
confidence: 54%
“…The in uence of ABO blood types on the release of endothelial cell injury molecules can have a substantial effect on the occurrence of organ failure in sepsis. The expression of markers indicating endothelial cell damage, such as sTM, syndecan-1, and sICAM-1, was found to be lower in patients with blood type B compared to those with other blood types 10,16 . This could explain that septic patients with blood type B had a lower frequency of newly d/eOD within 7 days after admission to ICU.…”
Section: Discussionmentioning
confidence: 87%
“…One possible explanation is that patients with blood type O tend to have plasma vWF levels that are 25-30% lower than those with other blood types, thereby impairing sepsisrelated coagulation and immunological responses 9 . However, a retrospective study conducted in Denmark revealed that septic patients with blood type B exhibited a slightly lower risk of 30-day mortality compared to septic patients with non-B blood type, which can be attributed to reduced endotheliumdamage 10 . To date, there is a scarcity of research investing the relationship between ABO blood type and the occurrence of organ dysfunction during the early stages of sepsis.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study found that Japanese patients with O-type blood also experience higher mortality rates while undergoing treatment for septic shock compared to patients with other blood types. 17 However, attempts to replicate these results in other patient populations have been unsuccessful. For example, Kander et al reported one of the largest studies on the influence of ABO and RhD blood groups on mortality, including 29,512 patients in five subgroups with the main diagnoses of sepsis, septic shock, acute respiratory distress syndrome, cardiac arrest, and trauma.…”
Section: Discussionmentioning
confidence: 99%